STUDIES ON THE TOTAL COLUMN ATMOSPHERIC AEROSOL OPTICAL DEPTH, OZONE AND PRECIPITABLE WATER CONTENT IN THE TROPICS: A CASE STUDY OF MALAYSIA - Said Fhazli (LPPM Universitas Muhammadiyah Riau, 2011)
A Multifilter Rotating Shadowband Radiometer has been used to monitor the directly transmitted solar irradiance at six wavelength regions (413.9 nm, 494.6 nm, 612.7 nm, 670.8 nm, 868.0 nm and 939.1 nm) for three clear stable days at Bangi. Extensive observations of the columnar aerosol optical depth (AOD), total column ozone (TCO) and precipitable water content (PWC) have been carried out using this instrument. The result shows that the maximum optical depth of aerosol at the shorter wavelength, especially on 24th February 2002 with mean value of 0.254 (24th February 2002), 0.095 (25th February 2002), and 0.072 (26th February 2002) while the ozone optical depth shows the mean value 0.0153 on 24th February 2002, 0.0174 on 25thFebruary 2002 and 0.0175 on 26th February 2002 with the avarage absorption coefficient (a), 0.2 (24th and 26th February 2002) and 0.1 (25th February 2002). The mean value of water vapor content shows that  = 0.356 cm and k = 0.301 cm for wavelength 939.1 nm. From the aerosol optical depth, it shows the existence of smoke type of aerosol on February, 24th to 25th 2002 with Ångström coefficient, , is 1.534 and 1.5513, respectively, and sea water vapor is 0.9889 on 26thFebruary 2002. From the Ångström coefficient, it shows that atmosphere layer of Bangi at that moment is similar to U.S. Standard Atmosphere, with maximum spectral irradiance on black body temperature is 5860 oK.